Pengolahan Rambut Jagung Untuk Teh Herbal Dan Strategi Pemasarannya - Leffy Hermalena; Herda Gusvita; Nita Yessirita; Bustari Badal; Rera Aga Salihat; Rera Agung Syukra; Inawaty Sidabalok; Henny Puspita Sari; Rina Febrinova (LPPM Universitas Ekasakti, 2024)
Corn silk (Zea mays L.), commonly considered agricultural waste, contains bioactive compounds with potential health benefits, including flavonoids, phenols, and tannins. These compounds exhibit antioxidant properties that can help prevent degenerative diseases such as cardiovascular disorders, diabetes mellitus, and cancer. This community service program focuses on utilizing corn silk as a raw material for producing herbal tea with economic value and health benefits. The program employs participatory and collaborative approaches, involving local farmers to develop skills in production, marketing, and product quality assurance. The innovation supports sustainable health practices and contributes to local economic development by transforming agricultural waste into valuable products.